Industrialization and management - "Paul, Samuel" (Bombay, 1977)
The essay in this volume deal with a set of important problems of industrial development which have been of con cern to India's policy-makers, administrators and citizens over the past decade. The major problem areas covered here include some aspects of industrial performance and policy, the economic environment of industry, the competitiveness of industrial exports, cost-benefit analysis of investments rele vant to industry, and the management of enterprises with special reference to the public sector. Admittedly, this col lection of essays is not meant to be an exhaustive treatise on all dimensions of these problems.
Keywords: Industrialization